An Examination of the Effectiveness of the Internal Control System at Department X in West Java Province - Eli Yualina; Patria Prasetio Adi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Enhancing governance and reinforcing public accountability are pivotal objectives in Indonesia’s ongoing bureaucratic reform, particularly through the application of the Government Internal Control System (SPIP). Despite being regulated at the national level, the operational effectiveness of SPIP within local institutions still encounters various challenges. This research investigates how SPIP is implemented within a Local Government Agency (OPD) in West Java Province, utilizing the five core components stipulated in Government Regulation No. 60 of 2008 and the maturity level indicators set by the Financial and Development Supervisory Agency (BPKP). The evaluation covers three components: objective setting, structure and processes (which include elements such as control environment, risk identification, control activities, information and communication flow, and monitoring processes), and the achievement of SPIP objectives. The analysis also incorporates the Risk Management Index (MRI) and the Corruption Control Effectiveness Index (IEPK). The results indicate that both SPIP and MRI are positioned at maturity level 3 (Defined), whereas IEPK stands at level 4 (Transformed), suggesting that while frameworks are established, they lack comprehensive integration and systematic documentation. These insights underline the urgency of reinforcing internal monitoring, integrating risk control across units, and leveraging digital tools for oversight. The study offers strategic insights for enhancing public sector internal control systems using adaptive and evidence-based practices.